Brood size moderates associations between relative size, telomere length, and immune development in European starling nestlings. Issue 22 (17th October 2016) - Nettle, Daniel; Andrews, Clare; Reichert, Sophie; Bedford, Tom; Gott, Annie; Parker, Craig; Kolenda, Claire; Martin‐Ruiz, Carmen; Monaghan, Pat; Bateson, Melissa
Abstract: For young birds in a nest, body size may have implications for other aspects of development such as telomere length and immune function. However, it is possible to predict associations in either direction. On the one hand, there may be trade‐offs between growth and telomere maintenance, and growth and investment in immune function, suggesting there will be negative correlations. On the other hand, relatively larger individuals might be advantaged in competition with their nest‐mates, allowing them to garner more resources overall, leading to positive correlations. We studied development over the nestling period in 34 nests of wild European starlings, Sturnus vulgaris . Intrabrood competition is typically more intense in larger broods. Hence, we predicted that body size should become an increasingly positive predictor of telomere length and immune functioning as brood size increases. In partial support of our prediction, there were significant interactions between brood size and body size in predicting both erythrocyte telomere length change and plasma levels of the cytokine interleukin‐6. The associations between body size and these outcomes went from negative in the smallest broods to positive in the largest. A further immune marker, high‐sensitivity C‐reactive protein, showed no systematic patterning with body size or brood size. Our results confirm that the size to which a nestling grows is important for telomere dynamics and the development of the immune system, but the phenotypic associations are moderated by the competitive context. Abstract : Is it beneficial or costly to be larger if you are a starling nestling? We test the hypothesis that the answer depends on the context: If competition is high, it is advantageous to be larger in order to win out; if competition is low, then energy spent on growing large is energy not spent on other functions. In accordance with this hypothesis, we show that the size of the brood moderates the association between body size and telomere attrition during the nestling period.